2006
DOI: 10.1007/s00436-006-0196-x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis sp. from white-fronted goose (Anser albifrons): cyst morphology and life cycle studies

Abstract: An experiment was carried out using three cubs of the arctic fox (Alopex lagopus). Twenty-five-day-old cubs were infected by feeding them with the leg muscles of the white-fronted goose (Anser albifrons) containing Sarcocystis sp. (cyst type III) cysts. Under the light microscope, the cysts were ribbon-shaped up to 4 mm long and up to 750 microm wide. On the surface of the wall (up to 2.4 microm), they had teat- or finger-like villar protrusions. Ultrastructurally, the cyst wall was a type-9 with villar protru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…Species whose hosts are birds create the greatest ambiguity. The results of our earlier investigations (Kutkienė and Sruoga 2004;Kutkienė et al 2006) showed that morphological parameters of the walls and cystozoites (very specific shape) of type III cysts found in the white-fronted (Anser albifrons), grey-lag (A. anser) and the lesser white-fronted (A. erythropus) geese are very similar. This suggested that the same Sarcocystis species may parasitise members of the Anser genus; however, to answer this question, first and foremost, data on ultrastructure and DNA of the cysts isolated from different species of birds are needed.…”
Section: Discussionmentioning
confidence: 51%
“…Species whose hosts are birds create the greatest ambiguity. The results of our earlier investigations (Kutkienė and Sruoga 2004;Kutkienė et al 2006) showed that morphological parameters of the walls and cystozoites (very specific shape) of type III cysts found in the white-fronted (Anser albifrons), grey-lag (A. anser) and the lesser white-fronted (A. erythropus) geese are very similar. This suggested that the same Sarcocystis species may parasitise members of the Anser genus; however, to answer this question, first and foremost, data on ultrastructure and DNA of the cysts isolated from different species of birds are needed.…”
Section: Discussionmentioning
confidence: 51%
“…The walls of these sarcocysts in few details resembled type-9 cyst wall (Dubey et al 1989), which we described for Sarcocystis sp. (cyst type III) from the white-fronted goose (Anser albifrons) (Kutkienė et al 2006). However, the villar protrusions of Sarcocystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…(cyst type I) from the white-fronted geese can be birds of prey, which are definitive hosts of protists of the Frenkelia genus rather than the representatives of the canine family, as has been preliminarily detected for Sarcocystis sp. (cyst type III) from the white-fronted geese (Kutkienė et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations